2020
DOI: 10.1016/j.ijscr.2020.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Oh, My Gauze !!!- A rare case report of laparoscopic removal of an incidentally discovered gossypiboma during laparoscopic cholecystectomy

Abstract: Highlights Gossypiboma, textiloma and cottonoid foreign bodies are discussed. Measures to avoid retaining surgical items are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…A surgical sponge is the most frequently retained surgical foreign body (69%), while other retained items include forceps, electrodes, needles, and retractors [5,9,11]. Gossypiboma has been reported after all types of surgeries, including gastrointestinal [2,12], gynecological [1,3,6], urological, vascular, orthopaedic, and spinal surgeries [13]. Gawande et al identified emergency procedures, unplanned changes in the surgical procedure, and obesity as the risk factors for the occurrence of retained sponges [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A surgical sponge is the most frequently retained surgical foreign body (69%), while other retained items include forceps, electrodes, needles, and retractors [5,9,11]. Gossypiboma has been reported after all types of surgeries, including gastrointestinal [2,12], gynecological [1,3,6], urological, vascular, orthopaedic, and spinal surgeries [13]. Gawande et al identified emergency procedures, unplanned changes in the surgical procedure, and obesity as the risk factors for the occurrence of retained sponges [14].…”
Section: Discussionmentioning
confidence: 99%
“…The foreign-body reaction makes the surgical removal of gossypiboma difficult, especially by minimally invasive technique. There are very limited reports on laparoscopic removal of the gossypiboma [1][2][3]. However, if feasible, laparoscopy offers the advantages of decreased postoperative pain, wound-related complications, and faster recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, laparoscopy can prove to be beneficial with its advantages of early ambulation, reduced post-op pain, cosmetically improved results and shorter length of hospital stay. There are limited case reports of laparoscopic removal of gossypiboma and therefore this approach should be encouraged to minimize morbidity to the patient [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 These cases are frequently diagnosed as abdominal neoplasms on sonology, or even diagnosed accidentally during another surgery. [5][6][7]…”
Section: Introductionmentioning
confidence: 99%